Implementasi Ta’dzim Santri Kepada Kyai dalam Lingkungan Pesantren Perspektif Pedagogi Relasional - Siti Maryam (Lakpesdam PCNU Kota Salatiga, 2023)
Ta’dzim (reverence) of santri toward kiai and teachers constitutes a fundamental value within the tradition of pesantren education and Indonesian Islam. Ta’dzim is not merely understood as an individual ethical attitude, but also as a socio-pedagogical mechanism in the transmission of knowledge, character formation, and the internalization of Islamic values. This article aims to analyze the concept and practice of ta’dzim santri from the perspective of relational pedagogy. This study employs a library research method with a qualitative-descriptive approach, critically examining classical pesantren texts, scholarly works by Muslim scholars, and reputable peer-reviewed journal articles on Islamic education, teacher–student relationships, and relational pedagogy. The findings reveal that ta’dzim functions as a relational foundation in Islamic education, emphasizing ethical, dialogical, and affective relationships between santri and kiai as prerequisites for educational success. Through the lens of relational pedagogy, ta’dzim is understood not as a repressive hierarchical relationship, but as an educational relationship that fosters trust, exemplarity, and moral responsibility. This study concludes that ta’dzim santri holds strong pedagogical relevance in character building, sustaining scholarly traditions, and shaping learning ethos in contemporary Islamic education.